2021
DOI: 10.1055/s-0040-1722162
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Nasal Obstruction after Septoplasty: A Single Institution Prospective Observational Study

Abstract: Introduction Nasal obstruction is a common symptom in otorhinolaryngological practice. It can impact significantly on the quality of life of the individual. Objective The primary goal of the present study was to evaluate quality of life after septoplasty in adults with nasal obstruction. A secondary goal was to assess the effectiveness of septoplasty. Methods This was a single institution prospective observational study. Patients had experienced septal deviation and symptomatic nasal obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Likewise, a recent study assessing the outcomes of nasal septoplasty in 51 patients using NOSE scores found significant improvements in nasal obstruction 3 and 7 months postoperatively. The mean preoperative and 3- and 7-month postoperative NOSE scores were 60.3±20.4, 32.9±16.8, and 39.6±33.2, respectively 20…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, a recent study assessing the outcomes of nasal septoplasty in 51 patients using NOSE scores found significant improvements in nasal obstruction 3 and 7 months postoperatively. The mean preoperative and 3- and 7-month postoperative NOSE scores were 60.3±20.4, 32.9±16.8, and 39.6±33.2, respectively 20…”
Section: Discussionmentioning
confidence: 95%
“…The mean preoperative and 3-and 7-month postoperative NOSE scores were 60.3 ± 20.4, 32.9 ± 16.8, and 39.6 ± 33.2, respectively. 20 . By comparison, the mean 3-month postoperative score in this study (15.0 ± 18.6) was considerably lower.…”
Section: Discussionmentioning
confidence: 99%
“…Besides septoplasty, there are many other interventions (both surgical and medical) that can be evaluated using the NOSE questionnaire, such as intranasal steroid, radiofrequency ablation, and functional septorhinoplasty. 14 , 30 , 31 , 32 The Thai‐NOSE appears to be helpful for documentation and discrimination of patients suffering from various degrees of nasal airway obstruction. However, the NOSE is limited only to subjective clinical reports of nasal airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…This validated instrument not only aims to assess the severity of nasal airway obstruction but also the clinical outcomes after therapeutic approaches. Besides septoplasty, there are many other interventions (both surgical and medical) that can be evaluated using the NOSE questionnaire, such as intranasal steroid, radiofrequency ablation, and functional septorhinoplasty 14,30‐32 . The Thai‐NOSE appears to be helpful for documentation and discrimination of patients suffering from various degrees of nasal airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with an increased influx of routine visits to the clinic, disturbed regular life style of people has made septoplasty the third most common surgical procedure performed 5 . Nasal septal surgeries has been significant is relieving the poor quality of life due to nasal obstruction 6 .…”
Section: Introductionmentioning
confidence: 99%